1108. Diagnostic Yield of the BioFire FilmArray Gastrointestinal Panel in Hospitalized Children at an Academic Children's Center. (26th November 2018) - Madigan, Theresa; Rajapakse, Nipunie; Patel, Robin
Abstract: Background: The BioFire FilmArray Gastrointestinal Panel (BioFire Diagnostics) (GIP) is a multiplex stool PCR test that detects 22 organisms. Studies in adults suggest that the diagnostic yield of the GIP in hospitalized patients is low. The utility of the GIP among hospitalized pediatric patients and indications for diagnostic stewardship of this test are not well described. Methods: We conducted a retrospective chart review of hospitalized pediatric patients who had a GIP ordered between October 2015 and October 2017. Demographic, clinical, and laboratory information was extracted from the medical record. Statistical analysis was completed using JMP Pro 13.0.0 (SAS Institute Inc.). Results: Over the 2-year study period, 193 GIPs were obtained on 155 individual pediatric patients. The mean patient age was 8 years and 59% were male. Forty-four percent of patients were immunocompromised and 21% had inflammatory bowel disease. The pediatric infectious disease (PID) team was consulted in 15% of patients at the time the test was ordered. The overall positivity rate of the GIP for one or more pathogens was 42% (Figure 1), with 76% of GIPs positive for one, 23% for two, and 1% for three pathogens. No parasitic infections were diagnosed. The GIP was more likely to be positive if GI symptom onset was prior to admission (48% vs. 24%, P = 0.004), if GI symptoms had been present for < 2 weeks vs. ≥2 weeks (52% vs. 20%, P = 0.0001), and if GI symptoms were the primary reason for the hospital admission (50% vs. 32%, P = 0.012). Only Clostridioides difficile or viral pathogens were detected in patients whose symptoms began in the hospital (Figure 2). Among patients with a positive test, 40% received treatment targeted at one or more of the detected pathogens (Figure 1). Enteropathogenic E.coli (EPEC) and Enteroaggregative E.coli (EAEC) were never treated (Figure 3). Conclusion: The GIP was positive for one or more pathogens in 42% of hospitalized children for whom the test was ordered, and led to specific therapy in 40% of those with a positive test. EPEC and EAEC were not treated. The diagnostic yield of the GIP was higher if GI symptoms were present for <2 weeks, began before hospitalization, and were the primary reason for admission. The GIP was frequently obtained without guidance from the PID team. Disclosures: R. Patel, CD Diagnostics, BioFire, Curetis, Merck, Hutchison Biofilm Medical Solutions, Accelerate Diagnostics, Allergan, and The Medicines Company: Grant Investigator, Research grant – monies paid to Mayo Clinic. Curetis, Specific Technologies, Selux Dx, GenMark Diagnostics, PathoQuest and Genentech: Consultant and Scientific Advisor, Consulting fee – monies paid to Mayo Clinic. ASM and IDSA: Travel reimbursement and editor's stipends, Travel reimbursement and editor's stipends. NBME, Up-to-Date and the Infectious Diseases Board Review Course: Varies, Honoraria. Mayo Clinic: Employee, Salary.